2021
DOI: 10.7150/ijms.58889
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Evaluation of All-Cause Mortality Risk and Survival Analysis for Hospitalized Patients with COVID-19

Abstract: Background: Coronavirus disease 2019 (COVID-19) has caused over 3.8 million deaths globally. Up to date, the number of death in 2021 is more than that in 2020 globally. Here, we aimed to compare clinical characteristics of deceased patients and recovered patients, and analyze the risk factors of death to help reduce mortality of COVID-19. Methods: In this retrospective study, a total of 2719 COVID-19 patients were enrolled, including 109 deceased patients and 2610 recovered patients. Medical records of all pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In an observational study from China, the mean d-dimer concentration was significantly higher in nonsurvivors compared with survivors 16 . Similarly, another retrospective Chinese study showed elevated levels of d-dimer (5.35 mg/l vs. 0.98 mg/l) in deceased patients as compared to the survivors of COVID-19 17 . Several studies have corroborated that elevated levels of d-dimer levels are associated with disease severity and mortality rates 6 , 9 .…”
Section: Introductionmentioning
confidence: 80%
“…In an observational study from China, the mean d-dimer concentration was significantly higher in nonsurvivors compared with survivors 16 . Similarly, another retrospective Chinese study showed elevated levels of d-dimer (5.35 mg/l vs. 0.98 mg/l) in deceased patients as compared to the survivors of COVID-19 17 . Several studies have corroborated that elevated levels of d-dimer levels are associated with disease severity and mortality rates 6 , 9 .…”
Section: Introductionmentioning
confidence: 80%
“…It has been demonstrated that metabolic abnormalities are positively correlated with the severity and prognosis of patients with ARDS. Furthermore, elevated blood glucose level is an independent risk factor for predicting the prognosis of ARDS patients 29,30 . Moreover, hyperglycemia at admission is positively associated with poor outcomes of patients in ICU 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, elevated blood glucose level is an independent risk factor for predicting the prognosis of ARDS patients. 29 , 30 Moreover, hyperglycemia at admission is positively associated with poor outcomes of patients in ICU. 31 On the other hand, lymphocytes are indicators of immunity and their suppression shows a damaged immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Летальность пациентов с сепсисом и ПОН в ОРИТ до стигает 50 % [44][45][46][47]. В период пандемии коронавирус ной инфекции летальность при развитии СШ превыша ла 80 % [48,49]. Таким образом, актуальность проблемы очевидна; в связи c этим целью данных клинических рекомендаций стала разработка мер по улучшению диагностики и результатов лечения СШ.…”
Section: эпидемиология септического шокаunclassified